ANALISIS PERAN KEPEMIMPINAN DALAM ADOPSI TEKNOLOGI BARU DI PERUSAHAAN MANUFAKTUR - Jopinus Saragih; Adrian K. Tarigan; Idayanti Adelina Silalahi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This article examines the role of leadership in the adoption of new technologies in manufacturing firms, particularly in the context of digital transformation driven by artificial intelligence (AI), the Internet of Things (IoT), and automation. The study aims to explain how leadership affects the success of technology implementation, identify challenges related to human and organizational factors, and review effective leadership strategies for integrating technological innovation into company operations. The research method is a literature study combined with qualitative and quantitative analysis by synthesizing various sources, including market reports, case studies, and academic research. The findings indicate that visionary and transformational leadership significantly improves employee acceptance through clear communication, the building of an innovation culture, intensive training, and effective change management. Nevertheless, adoption success is also influenced by barriers such as limited internal expertise, resistance to change, difficulties integrating legacy systems, and the need to prioritize data security. The article recommends strategies including active employee involvement, continuous training, planned system integration, strengthening digital infrastructure, and developing digital leadership to ensure that transformation is effective and sustainable.